Chemical vapour deposition of poly(p-phenylenevinylene) nanofilms for use in organic photovoltaics - Supangat, A.; Zhou, X.J.; Belcher, W.; Dastoor, P. (Springer Verlag (Germany), 2011)
Poly(p-phenylenevinylene) (PPV) nanofilms have been successfully synthesised via chemical vapour deposition for use in organic photovoltaics (OPVs). A bilayer OPV structure was fabricated by incorporating a layer of PPV as an electron donor and [6,6]-phenyl-C61-butyric acid methyl ester as an electron acceptor. The photovoltaic properties of these devices are discussed.